Археологічні дослідження середньовічних пам’яток Харкова у 2008 р. - Голубєва, І.В. (Археологічні дослідження в Україні, 2009)
The article contains concise information about the results of protective archaeological excavations undertaken on the territory of dytynets (citadel, at 11, Kvitka-Osnovyanenko Street) and of posad (trading quarters, at 8, Klochkovska Street) of Kharkiv fortress, as well as at the discovered settlement of the 1st millennia AD in Novo-Chuykivska Street. For the first time, in the historic centre of the city a layer and structures with Ancient Rus and imported synchronous ceramics have been recorded.